Effect of Bentonite and FYM on the Growth and Yield of Wheat - paliwal, K.V.; Lavti, D.L. (Journal of Soil and Water Conservation, 2022)
About two third of Rajasthan soils are light textured and are generally poor in fertility status and soil structure. Such soils are easily subjected to wind erosion and maintainance of a proper physical condition of such soils is of primary importance. Addition of organic matter and any suitable binding agent of smaller size are the common practices adopted for this purpose. But due to low and uncertain rainfall, high tempera-ture, rapid rate of decomposition of organic matter and limited availability of F.Y.M., soil organic matter is quite inadequate. Under this situation it would be of great use to find out the effect of a cementing agent which could bind the loose soil particles, improve soil physical condi-tion and stablise the organic matter.